Flavonoids as Important Molecules of Plant Interactions with the Environment - Mierziak, Justyna (Molecules, 2014)
Flavonoids are small molecular secondary metabolites synthesized by plants with various biological activities. Due to their physical and biochemical properties, they are capable of participating in plants’ interactions with other organisms (microorganisms, animals and other plants) and their reactions to environmental stresses. The majority of their functions result from their strong antioxidative properties. Although an increasing number of studies focus on the application of flavonoids in medicine or the food industry, their relevance for the plants themselves also deserves extensive investigations. This review summarizes the current knowledge on the functions of flavonoids in the physiology of plants and their relations with the environment.